Antifouling Mussel-Inspired Hydrogel with Furanone-Loaded ZIF-8 for Quorum Sensing-Mediated Marine Antifouling - Yanbin Xiong; Junnan Cui; Xiaodan Liu; Haobo Shu; Pan Cao (Gels, 2025)
Marine biofouling, the process of marine microorganisms, algae, and invertebrates attaching to and forming biofilms on ship hulls, underwater infrastructure, and marine equipment in ocean environments, severely impacts shipping and underwater operations by increasing fuel consumption, maintenance costs, and corrosion risks, and by threatening marine ecosystem stability via invasive species transport. This study reports the development of a hydrogel-metal-organic framework (MOF)-quorum sensing inhibitor (QSI) antifouling coating on 304 stainless steel (SS) substrates. Inspired by mussel adhesion, a hydrophilic bionic hydrogel was first constructed via metal ion coordination. The traditional metal ion source was replaced with a zeolitic imidazolate framework-8 (ZIF-8) loaded with 2-(5H)-furanone (HF, a QSI) without altering coating formation. Physicochemical characterization using Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), the Brunauer–Emmett–Teller (BET) method, and the diffraction of x-rays (XRD) confirmed successful HF loading into ZIF-8 with intact crystal structures. Antifouling tests showed HF@ZIF-8 enhanced antibacterial inhibition against Staphylococcus aureus (97.28%) and Escherichia coli (>97%) and suppressed Chromobacterium violaceum CV026 pigment synthesis at 0.25 mg/mL (sub-growth concentration). The reconstructed PG/PVP/PEI/HF@ZIF-8 coating achieved 72.47% corrosion inhibition via synergistic anodic protection and physical shielding. This work provides a novel green approach for surface antifouling and drag reduction, highlighting MOF-loaded QSIs as promising additives to enhance the antifouling performance of hydrogel coatings, anti-corrosion performance, and QSI performance for sustainable marine engineering applications.